Ta’līm al-Lugah al-‘Arabīyah ‘an ṭarīq ta’līm al-bī’ah al-‘arabīyah: Dirāsah Muqāranah Baina Daurah Ocean li Ta’līm al-Lugah al-‘Arabīyah wa Markaz al-Daurāt al-Islāmīyah li al-Lughah al-‘Arabīyah fī Pare Kediri - Faizi, Ach. Wildan Al (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
This study aims to identify the state of the Arabic environment and provide solutions to problems in the formation of the environment for suggestions in language acquisition. From a theoretical point of view, it can be used as a source of knowledge about language acquisition and environment formation. This research follows a qualitative approach and descriptive research type.  The results of this research show that the Oshian Arabic language course and the Islamic courses center have similarities and differences in Arabic language teaching. Both use the environment as a tool in the Arabic teaching process. The difference between them lies in the learning methods and strategies used in the classroom. The Oshian course focuses more on language skills, while the Islamic Courses Center focuses on understanding grammar. There are many extracurricular activities in the language environment of the Oshian course and the Islamic Courses Center.